A Novel Energy Harvesting-Enabled Design for Radar and Communication Coexistence - Jiang, Zheng-Ming; Zhang, Peichang; Huang, Lei; Rihan, Mohamed; Zhang, Jihong (Asian and Pacific Conference on Synthetic Aperture Rader proceedings (APSAR), 2019)
In this paper, we propose a novel energy harvesting-enabled MIMO radar and communication coexisting model. In this model, the transmitter beamformes the same signal to be received at both the energy harvesting receiver and the information receiver to realize the concept of simultaneous wireless information and power transfer. Specifically, a monostatic MIMO radar transmits its signal to an energy-harvesting-receiver which in turn can feed low-power devices, and at the same time this signal can be employed target detection purposes. A radar detection probability maximization problem is formulated subject to constraints on the performance of the communication, radar and energy harvesting. The waveform of radar and communication are optimized to maximize radar detection probability. A proposed method has been introduced to solve the optimization problem. The simulation results prove the superiority of the proposed method compared to traditional counterparts.